2018
DOI: 10.3390/pharmaceutics10010027
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Sunscreen Safety: Effects of the Vehicle and Repeated Applications on Skin Permeation from Topical Formulations

Abstract: The evaluation of UV-filter in vitro percutaneous absorption allows the estimation of the systemic exposure dose (SED) and the margin of safety (MoS) of sunscreen products. As both the vehicle and pattern of application may affect sunscreen safety and efficacy, we evaluated in vitro release and skin permeation of two widely used UV-filters, octylmethoxycinnamate (OMC) and butylmethoxydibenzoylmethane (BMBM) from topical formulations with different features (oil in water (O/W) emulsions with different viscosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…As widely reported in the literature, vehicles can strongly affect the performance of cosmetic products, including sunscreen formulations [8,9,[21][22][23][24][25][26]. The effectiveness of sunscreens and their compliance with consumer expectations requires that the product be easily spread onto skin, leaving a thin, uniform, adhering, and water-resistant film on the cutaneous surface.…”
Section: Of 10mentioning
confidence: 99%
See 1 more Smart Citation
“…As widely reported in the literature, vehicles can strongly affect the performance of cosmetic products, including sunscreen formulations [8,9,[21][22][23][24][25][26]. The effectiveness of sunscreens and their compliance with consumer expectations requires that the product be easily spread onto skin, leaving a thin, uniform, adhering, and water-resistant film on the cutaneous surface.…”
Section: Of 10mentioning
confidence: 99%
“…Recently, selected herbal oils have been investigated to develop sunscreen formulations with a reduced content of organic UV-filters while still maintaining a high sun protection factor (SPF) [4][5][6]. Indeed, the safety of organic UV-filters has been widely debated because some studies on the skin penetration and permeation of these molecules have reported that they are able to permeate the skin at sufficient rates to be recovered from systemic circulation [7][8][9]. Therefore, to address the safety issue of organic UV-filters, several researchers performed in vivo toxicity studies from which the margin of safety (MoS) was calculated by comparing the potential human systemic exposure with the no adverse effect level (NOAEL) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, we are reminded by Montenegro et al [13] that enhanced skin penetration may not always be a desirable outcome. When it comes to sunscreen safety, the aim is to limit skin penetration of chemicals from the topical formulations to avoid toxicity.…”
mentioning
confidence: 85%
“…Even though the ability of some solvents to promote delivery of EA across porcine skin in vitro has been confirmed, the permeability of the compound was comparatively low, with 0.6% to 7.5% of the applied dose delivered after 24 h. Additionally, commonly used excipients and/or penetration enhancers such as ethoxydiglycol, dipropylene glycol, 1,5 pentanediol, and tripropylene glycol did not promote permeation of EA through porcine skin [5]. Generally, it is accepted that skin permeation of actives is vehicle-dependent [7,8] and combinations of solvents have been shown to act synergistically to enhance permeation of compounds [9][10][11].…”
Section: Introductionmentioning
confidence: 91%